Investor Sentiment Role on Asset Pricing in Emerging Markets During Stock Markets Crisis: Application to Egyptian Market Using Fuzzy Regression - Heshmat, Nesma; Abdallah, Hisham (The Arab Journal of Administration, 2019)
The purpose of this study is to investigate the investors sentiment in the emerging markets and analyze its role could improve the well-known models like Fama-French Model by using Fuzzy Regression. The Egyptian stock has witnessed two crises, the first is world financial crisis in 2008 and the second is in 2011 as a result of the Egyptian revolution. The study will analyze the role of investor’s sentiment on the asset pricing during the stock crisis. To capture the effect of the stock crisis the data sample include one year before 2008 crisis, during 2008 crisis, from 2009 till 2010, during 2011 crisis and three years after the 2011 crisis. The study employs methodologies proposed in literatures to construct investor sentiment index for the period. The results conduct the importance role of investor sentiment on asset pricing.